Zachariasz – kapłan, ojciec, ofiarnik - Mielcarek, Krzysztof W. (The Biblical Annals, 2017)
Zachariah does not belong to the group of main protagonists of the New Testament. He is even hardly a main figure of Lucan two-volume work. And yet, he does play some important role in the narrative of Luke-Acts. Putting him into the first scene of the Infant narrative and juxtaposing him with Mary, Mother of Jesus, are very clear signs of it. While the full picture of Zechariah is drawn in three consecutive scenes: the annunciation in the Temple (Łk 1,5-25); the birth of John (1,57-66) and Zechariah’s prophecy called „Benedictus” (1,67-80), two of his main features are especially elaborated: his priesthood and fatherhood. The paper gathers Lucan evidence on the matter showing that to the third evangelist Zechariah is a very special kind of father